Para vaginal Dermoid Cyst: A Diagnostic Dilemma - Saha, J; Akter, S; shetu, Sf; Sultana, T (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Dermoid cyst (cystic teratoma) is a benign germ cell tumour showing well differentiated derivatives of all three germs cell layers. Ovaries remain the commonest site. Paravaginal dermoid cyst is a rare occurrence. A 48years’ female presented with paravaginal cyst, (9.11x7) cm. The diagnosis of a suspected ovarian tumor was made and an exploratory laparotomy was done. On dissection, the lower margin could not be identified. So lower limit of the cyst was dissected through vaginal approach. Transvaginal excision of dermoid cyst under anaesthesia remains treatment of choice. Retrospective diagnosis on histopathological examination remains confirmatory as it may be missed on sonography if teeth are not present in dermoid cyst. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 120-123